2003
DOI: 10.1046/j.1365-2427.2003.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

Midsummer spatial variation in methane efflux from stands of littoral vegetation in a boreal meso‐eutrophic lake

Abstract: Summary 1. Spatial variation of methane (CH4) efflux from the littoral zone of a meso‐eutrophic boreal lake was studied with a closed‐chamber technique for three summer days in 22 vegetation stands, consisting of three emergent and three floating‐leaved species. 2. Between‐species differences in CH4 emission were significant. The highest emissions were measured from the emergent Phragmites australis stands (0.5–1.7 mmol m−2 h−1), followed by Schoenoplectus lacustris > Equisetum fluviatile > Nuphar lutea > Spar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
(76 reference statements)
3
24
0
Order By: Relevance
“…The littoral zone of lakes has been regarded as hotspots of CH 4 fluxes through several studies (Juutinen et al, 2001;Kankaala et al, 2003;Wang et al, 2006;Hirota et al, 2007). In the present study we also found that CH 4 efflux from the littoral zone of Huahu Lake on the Qinghai-Tibetan Plateau was relatively high among those of boreal and temperate lakes (Juutinen et al, 2001, Kankaala et al, 2003, Wang et al, 2006; summarized in Table 4) and higher than those from alpine wetlands in the same region (Hirota et al, 2004;Chen et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The littoral zone of lakes has been regarded as hotspots of CH 4 fluxes through several studies (Juutinen et al, 2001;Kankaala et al, 2003;Wang et al, 2006;Hirota et al, 2007). In the present study we also found that CH 4 efflux from the littoral zone of Huahu Lake on the Qinghai-Tibetan Plateau was relatively high among those of boreal and temperate lakes (Juutinen et al, 2001, Kankaala et al, 2003, Wang et al, 2006; summarized in Table 4) and higher than those from alpine wetlands in the same region (Hirota et al, 2004;Chen et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…In the present study we also found that CH 4 efflux from the littoral zone of Huahu Lake on the Qinghai-Tibetan Plateau was relatively high among those of boreal and temperate lakes (Juutinen et al, 2001, Kankaala et al, 2003, Wang et al, 2006; summarized in Table 4) and higher than those from alpine wetlands in the same region (Hirota et al, 2004;Chen et al, 2008). This may be partly attributed to high dissolved organic carbon (DOC) input from nearby peatlands, whose soil is rich in organic carbon on the Qinghai-Tibetan Plateau (Wang et al, 2002).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The emergent macrophyte Schoenoplectus lacustris, for which we have tentative evidence for methane oxidation, has an aerenchymous system and has previously been identified as a conduit of methane from a lake (Kankaala et al 2003). It is a plausible host for a methane-oxidizing microbial community.…”
Section: Discussionmentioning
confidence: 75%
“…While a wealth of studies have dealt with CH 4 measurements in helophyte stands (van der Nat, and Middelburg 1998; Brix et al 2001;Kankaala et al 2005;Laanbroek 2010), few data are available for floating-leaved rhizophytes (Dacey, and Klug 1979;Smith, and Lewis 1992;Juutinen et al 2003;Kankaala et al 2003). Moreover, in a very limited number of studies the magnitude and seasonal trends of CO 2 and CH 4 fluxes across the vegetated surface were measured simultaneously (Bolpagni et al 2007).…”
Section: Introductionmentioning
confidence: 99%